Preparation and Characterization of Nay Zeolite for Biodiesel Production - Abbas, Ammar S.; Abbas, Rowaida N. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Iraqi kaolin was used for the preparation and characterization of NaY zeolite for biodiesel production via esterification reaction. Oleic acid was used usually as a typical simulated feedstock of high acid number for the esterification reaction.   The chemical composition for the prepared Nay zeolite is as following:  (Ca2.6Na1.K0.1)(Al6.3Si17.7)O48.16H2O, the silica to alumina ratio in the prepared catalyst was found equal to 2.6 and Na2O content was 12.26 wt. %, with relative crystallinity equal to 147.4 % obtained by the X-ray diffraction. The surface area result shows that the prepared catalyst has 330 m2/g. While, the measured pore volume by nitrogen adsorption was equal to 0.35 cm3/ g. SEM images show notable differences between the kaolin crystal and prepared NaY crystal.   The effect of NaY zeolite, as a loaded catalyst in the esterification of oleic acid reaction did not show any significant change of oleic acid conversion for catalyst load more than 5 wt. %. The reused NaY zeolite is loses 31 % of its activity because of that the pores are filled with water and other organic molecules and that may cause poisoning the catalyst.